THE SCIENTIFIC LEGACY OF ORIENTAL SCHOLARS IN THE DEVELOPMENT OF MATHEMATICAL SCIENCE - Botirova S. Ya; Djumabaev X.Yu; Mamajanov G. O (International Journal on Orange Technologies, 2020)
A student who is good at math will have a high level of analytical and logical thinking. It develops the ability to make quick decisions, discuss and negotiate, and do things step by step, not only in solving examples and problems, but also in different situations in life.